An email-based high capacity text steganography using repeating characters. Issue 3 (16th March 2021) - Fateh, Mansoor; Rezvani, Mohsen
ABSTRACT: Email steganography is one of the subcategories of text steganography. This subcategory is noted due to the widespread use of emails for communication. In this paper, we propose a new method for email steganography which provides a high level of capacity along with a strong security level. Furthermore, since no surplus information is added to the cover text, we can use any kinds of email bodies as the cover text. In order to provide a high level of security, we offer several stego keys. In the first step of the proposed scheme, the secret message is compressed by using one of the lossless compression algorithms named LZW to several bit streams. Then in every step, due to number of email body's characters, a part of each bit stream is selected and by using the email addresses will be created. The proposed method presents a capacity level of 10.6 over a common sample used by other studies, which proved a significant increase in term of capacity.